Pengaruh Reliability dan Responsiveness terhadap E-Loyalty yang Dimediasi oleh E-Satisfaction Point Coffee secara Online Food Delivery Order (OFDO) di Kota Bandung - Mulyawati, Ropita; Putra, Hariyadi Triwahyu (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to determine how variable responsiveness and reliability relate to each other through e-satisfaction measured by e-loyalty Point Coffee’s Online Food Delivery Order (OFDO) service in city of Bandung. The instruments used in ther work include double regression, validity tests, reliability tests, and tests of classical assumptions. Up to 120 respondents who made purchases online were counted as respondents using the instrument to gather data on Point Coffee’s clientele. SPSS 25 was used for testing. The result make it clear that responsiveness and reliability have a positive relationship with e-satisfaction, that responsiveness and reliability have a positive relationship with e-loyalty, that e-satisfaction influenes e-loyalty, and that e-satisfaction plays a mediating function in dependability. There was a difference from the provious study that Point Coffee was the object of the evaluation. These findings are expected to help future researchers and help Point Coffee product management relate to relevant plans.